2019
DOI: 10.1001/jamapsychiatry.2019.2309
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Maternal Anemia With Neurodevelopmental Disorders

Abstract: IMPORTANCE Given the critical role that iron plays in neurodevelopment, an association between prenatal iron deficiency and later risk of neurodevelopmental disorders, such as autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and intellectual disability (ID), is plausible. OBJECTIVE To test the a priori hypothesis that anemia diagnosed in mothers during pregnancy is associated with an increased risk of ASD, ADHD, and ID in offspring and that the magnitude of the risk varies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 40 publications
(82 reference statements)
3
117
0
9
Order By: Relevance
“…Neonatal iron deficiency has been linked to numerous neurobehavioral effects (4). Most recently, an association was reported between maternal anemia diagnosed earlier in pregnancy (≤30 weeks) and increased offspring risk of autism spectrum disorder, attention-deficit/hyperactivity disorder, and intellectual disability (6). Therefore, it is important that neonatal iron deficiency be accurately quantitated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal iron deficiency has been linked to numerous neurobehavioral effects (4). Most recently, an association was reported between maternal anemia diagnosed earlier in pregnancy (≤30 weeks) and increased offspring risk of autism spectrum disorder, attention-deficit/hyperactivity disorder, and intellectual disability (6). Therefore, it is important that neonatal iron deficiency be accurately quantitated.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is essential for a healthy pregnancy, with approximately 1 gram of iron needed for the expansion of maternal red cell mass and placental and fetal development (1). Severe iron deficiency and iron deficiency anemia during pregnancy have been associated with increased maternal mortality, perinatal death, preterm birth, low birth weight, impaired immune function, and long-term cognitive defects in newborns and infants (2)(3)(4)(5)(6). To prevent these adverse outcomes, the WHO currently recommends daily iron supplementation for all pregnant adolescent and adult women (7).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, timing, dose, and duration of the insufficiency determine the sequelae. In an analysis of over half a million of children in Sweden, it was shown that children of mothers who were diagnosed with anemia in the first 30 weeks of pregnancy had a higher incidence of autism spectrum disorder, ADHD, and intellectual disability relative to children of mothers who were diagnosed later in pregnancy or not diagnosed [26]. Thus, the earlier timing and longer duration of the insufficiency led to more severe and diagnosable issues.…”
Section: Ironmentioning
confidence: 99%
“…Maternal nutrition is a factor associated with ASD that might plausibly correlate with the presence of AGA. For example, maternal iron deficiency during the early stages of pregnancy has been associated with an increased risk of ASD in offspring (28). Cereals, including wheat, constitute an important source of iron in Sweden (29) and the reduced ASD risk associated with AGA may reflect wheat consumption and adequate iron supplies in a subgroup of women.…”
Section: Potential Mechanism and Implications For Asd Pathogenesismentioning
confidence: 99%